Advances in synthesis gas methods, technologies and applications. - Rahimpour, Mohammad Reza, 1961-; Makarem, Mohammad Amin; Meshksar, Maryam (Elsevier, 2022)
Advances in Synthesis Gas: Methods, Technologies and Applications: Syngas Production and Preparation is a collection of various chapters concerning many aspects of syngas production technologies, including common methods like gasification, steam/dry/autothermal reforming, membrane technology, etc., along with novel methods like plasma technology, micro-reactors, electrolysis processes as well as photocatalytic systems. In addition, different sources for producing syngas, including oil, crude oil, heavy oil, microalgae, black liquor, tar and bitumen, as well as municipal, agricultural, food, plastic, wood and cardboard wastes are described in detail.